Violations of coagulation hemostasis in patients with arterial hypertension in combination with osteoarthrosis - V. V. Rodionova; O. S. Khmel' (Zaporožskij Medicinskij Žurnal)
Objective: To define violations of coagulation hemostasis in patients with arterial hypertension (HT) and osteoarthrosis (OA).